Tetradecyl 2, 3-dihydroxybenzoate alleviates oligodendrocyte damage following chronic cerebral hypoperfusion through IGF-1 receptor. (September 2020) - Youssef, Mahmoud I.; Zhou, Yiting; Eissa, Ibrahim H.; Wang, Yanhui; Zhang, Jing; Jiang, Lei; Hu, Weiwei; Qi, Jianhua; Chen, Zhong
Abstract: Currently, there is no effective therapy for chronic cerebral hypoperfusion-induced subcortical ischemic vascular dementia (SIVD), which displays cognitive deficits and progressive white matter damage. Tetradecyl 2, 3-dihydroxybenzoate (ABG-001) is a lead compound derived from gentisides with neuritogenic activity. In this report, we intended to investigate the effect of ABG-001 on the SIVD experimental model through right unilateral common carotid arteries occlusion (rUCCAO) in mice. We found that ABG-001 remarkably alleviated white matter damage and cognitive deficits after cerebral hypoperfusion induced by rUCCAO. The protection of ABG-001 on the white matter was related to an amelioration of the oligodendrocyte apoptosis and demyelination rather than promoting remyelination. Molecular docking study showed that ABG-001 possesses a high affinity for insulin-like growth factor-1 receptor (IGF-1R), but not for tropomyosin receptor kinase A (TrkA). The protection of ABG-001 against oligodendrocyte damage was abrogated by IGF-1R antagonist or knockdown of IGF-1R through shRNA, but not TrkA antagonist. Moreover, ABG-001 did not induce hematological, renal or hepatic toxicity after chronic treatment. The present study indicates that ABG-001 protects oligodendrocytes through IGF-1R to relieve demyelination following chronic cerebral hypoperfusion, which could be represented as an encouraging treatment for SIVD. Highlights: ABG-001 remarkably alleviates white matter damage and cognitive deficits after cerebral hypoperfusion. The protection of ABG-001is related to an amelioration of oligodendrocyte damage through the activation IGF-1 receptor. ABG-001 has no apparent toxicity following chronic administration.